The Mediating Role of Hedonic and Utilitarian Behavior in the Influence of Parasocial Interaction on Youtube on a Female Beauty Product Purchase Intention - Indriyarti, Eko Retno; Murtiningsih, Retno Sari (Journal of Business & Applied Management, 2024)
The beauty product sector in Indonesia is currently experiencing intensifying competition. Recent research indicate that a beauty product is highly susceptible to problems within the cosmetics sector, particularly in Indonesia. This consistently elucidates that there are factors influencing the intensity of beauty product acquisitions. The objective of this study is to examine the factors influencing the frequency of Maybelline cosmetic product purchases among women in Indonesia. The characteristics that quantify buying intensity include parasocial interaction, hedonic behavior, and utilitarian conduct. This research employs a quantitative methodology via a survey with a questionnaire. This study had a total of 145 individuals. This study used purposive sampling by establishing criteria for participant selection, specifically targeting women residing in Jabodetabek, who are YouTube users and have viewed Maybelline beauty product review video on the platform. This study employs PLS-SEM modeling utilizing SmartPLS as the analytical tool. This study's results indicate that social interaction greatly affects hedonic, utilitarian, and purchasing intentions. Conversely, hedonic and utilitarian outcomes yield distinct results in elucidating their impact on buying intensity. This is also pertinent to the outcomes of the indirect effect. This study enhances the Unified Theory of Acceptance and Use of Technology by incorporating hedonic motivation as a significant factor in comprehending consumer technology uptake.